Effect of duration and exogenous carbohydrate on gross efficiency during cycling - Dumke, C. L.; McBride, J. M.; Nieman, D. C.; Gowin, W. D.; Utter, A. C.; McAnulty, S. R. (The Journal of Strength and Conditioning Research, 2007)
The purpose of this investigation was to determine the effects of 2.5 hours of cycling with and without carbohydrate supplementation on gross efficiency (GE). Trained cyclists (N = 15) were tested for vO2max (53.6 ° 2.2 ml/kg.min) and lactate threshold during incremental tests to exhaustion. On 2 separate visits, cyclists performed 2.5 hours of cycling on an indoor trainer. A carbohydrate (C) or placebo (P) beverage was randomly provided and counter- balanced for each of the trials. Gross efficiency, cycling economy, power output, vO2, lactate, and blood glucose were measured every 20 minutes during the 2.5-hour ride. Muscle glycogen was measured immediately before and after the ride from the vastus lateralis. Results indicated that power output and vO2 decreased over time (p < 0.05) but were not different between trials. Relative GE and cycling economy during C were greater than P at 40 and 150 minutes (p < 0.05). Blood glucose significantly decreased in P and was lower than C at all time points (p < 0.05). Respiratory exchange ratio decreased over time in both trials, with a significant treatment effect at 40 and 150 minutes (p < 0.05). Muscle glycogen decreased by 65% during both conditions (p < 0.05) but demonstrated no treatment effect. We conclude that carbohydrate supplementation during 2.5 hours of cycling attenuated the decrease in GE possibly by maintaining blood glucose levels. This suggests that the positive effect of carbohydrate supplementation on endurance performance may be through the maintenance of metabolic efficiency.